2017
DOI: 10.4172/2376-127x.1000305
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Obesity during Childhood: A Review of More than an Occasional Association

Abstract: Introduction: Asthma and obesity are both extremely prevalent diseases in children and their combination represents a different phenotype not explained by the simple addition of both diseases alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(55 reference statements)
0
0
1
Order By: Relevance
“…After a systematic review about obesity and asthma during childhood, it was concluded that an association between asthma and obesity in the pediatric population was extremely likely. 27 However, in the present study, although, asthma was positively associated with increased BMI Z score, this association disappeared when logistic regression was used to allow for effect of different socio-demographic and clinical factors. Findings of the present research were supported by other study.…”
Section: Discussioncontrasting
confidence: 68%
“…After a systematic review about obesity and asthma during childhood, it was concluded that an association between asthma and obesity in the pediatric population was extremely likely. 27 However, in the present study, although, asthma was positively associated with increased BMI Z score, this association disappeared when logistic regression was used to allow for effect of different socio-demographic and clinical factors. Findings of the present research were supported by other study.…”
Section: Discussioncontrasting
confidence: 68%